Developing a landscape‐scale, multi‐species, and cost‐efficient conservation strategy for imperilled aquatic species in the Upper Tennessee River Basin, USA. Issue 6 (29th June 2017) - Smith, David R.; Butler, Robert S.; Jones, Jess W.; Gatenby, Catherine M.; Hylton, Roberta E.; Parkin, Mary J.; Schulz, Cindy A.
Abstract: Strategic conservation of imperilled species faces several major challenges including uncertainty in species response to management actions, budgetary constraints that limit options, and the need to scale expected conservation benefits from local to landscape levels and from single to multiple species. A structured decision‐making process was applied to address these challenges and identify a cost‐effective conservation strategy for the Federally listed endangered and threatened aquatic species in the Upper Tennessee River Basin (UTRB). The UTRB, which encompasses a landscape of 58 000 km 2, primarily in western North Carolina, eastern Tennessee, and south‐western Virginia, harbours one of the most globally diverse assemblages of freshwater fishes and mussels at temperate latitudes. To develop a strategy for conservation of 12 fish species and 24 mussel species over a 20‐year period, a management strategy that would best recover these species was identified given costs and uncertainty in management effectiveness. The main insights came from a trade‐off analysis that compared alternative allocations of effort among management actions. A strategy emphasizing population management, which included propagation and translocation, performed best across a wide range of objective weightings and was robust to uncertainty in management effectiveness. Species prioritization was based on the expected conservation benefit from the best performing strategy, degree of imperilment, and species‐specific management costs. Sub‐basin prioritization was based on expected conservation benefit from the best performing strategy and feasibility of habitat management and threat abatement. Although the strategy was developed for imperilled aquatic species in the UTRB, the structured process is applicable for developing cost‐efficient strategies to conserve multiple species across a landscape under uncertain management effectiveness. The process can assist a manager with limited resources to understand which species to work on, where to conduct that work, and what work would be most beneficial for those species in those catchments.